Effects of the Dipeptidyl Peptidase-IV Inhibitor Vildagliptin on Incretin Hormones, Islet Function, and Postprandial Glycemia in Subjects With Impaired Glucose Tolerance - Rosenstock, Julio; Foley, James E; Rendell, Marc; Landin-Olsson, Mona; Holst, Jens J; Deacon, Carolyn F; Rochotte, Erika; Baron, Michelle A (Diabetes care, 2008)
OBJECTIVE:--This study was conducted to determine the effects of vildagliptin on incretin hormone levels, islet function, and postprandial glucose control in subjects with impaired glucose tolerance (IGT). RESEARCH DESIGN AND METHODS--A 12-week, double-blind, randomized, parallel-group study comparing vildagliptin (50 mg q.d.) and placebo was conducted in 179 subjects with IGT (2-h glucose 9.1 mmol/l, A1C 5.9%). Plasma levels of intact glucagon-like peptide 1 (GLP-1) and gastric inhibitory polypeptide (GIP), glucose, insulin, C-peptide, and glucagon were measured during standard meal tests performed at baseline and at week 12. Insulin secretory rate (ISR) was estimated by C-peptide deconvolution. The between-group differences (vildagliptin - placebo) in the adjusted mean changes from baseline to end point in the total and incremental (Δ) area under the curve (AUC)₀₋₂ h for these analytes were assessed by ANCOVA; glucose AUC₀₋₂ h was the primary outcome variable. RESULTS:--Relative to placebo, vildagliptin increased GLP-1 (ΔAUC, +6.0 ± 1.2 pmol · l⁻¹ · h⁻¹, P < 0.001) and GIP (ΔAUC, +46.8 ± 5.4 pmol · l⁻¹ · h⁻¹, P < 0.001) and decreased glucagon (ΔAUC, -3.0 ± 1.0 pmol · l⁻¹ · h⁻¹, P = 0.003). Although postprandial insulin levels were unaffected (ΔAUC, +20.8 ± 35.7 pmol · l⁻¹ · h⁻¹, P = 0.561), prandial glucose excursions were reduced (ΔAUC, -1.0 ± 0.3 mmol · l⁻¹ · h⁻¹, P < 0.001), representing an ~30% decrease relative to placebo. β-Cell function as assessed by the ISR AUC₀₋₂ h/glucose AUC₀₋₂ h was significantly increased (+6.4 ± 2.0 pmol · min⁻¹ · m⁻² · mmol · l⁻¹, P = 0.002). Adverse event profiles were similar in the two treatment groups, and no hypoglycemia was reported. CONCLUSIONS:--The known effects of vildagliptin on incretin levels and islet function in type 2 diabetes were reproduced in subjects with IGT, with a 32% reduction in postprandial glucose excursions and no evidence of hypoglycemia or weight gain.